The socio-cultural context of breastfeeding in the nineteenth and twentieth centuries - Runjić Babić, Anđela (Array, 2020)
This paper will give a historical account of breastfeeding and explain the socio-cultural context in which the shift from breastfeeding to bottle feeding occurred in the western industrialized nations in the course of the nineteenth and twentieth centuries. Whereas in the nineteenth century most infants were breastfed by the middle of the twentieth century bottle-feeding had become the norm. The growth of artificial infant feeding was related to economic conditions as well as the socio- cultural changes within the burgeoning industrial societies. Aside from the rise of infant formula industry one of the major factors that affected the decline in breastfeeding rates was the shift of breastfeeding from a natural practice into an object of medicine and science. Other cultural factors including religious beliefs, feminism and the changing roles of women within society have affected women's infant feeding choices. Throughout these socio-historical developments breastfeeding was promoted as the best option for infant health. However, concern over breastfeeding rates was also a concern over women's proper mothering behavior and a desire to control women and their mothering practices.